Phonological analysis of aphasic speech - Neena Suri (Journal of All India Institute of Speech and Hearing, 1970)
The phonological research in aphasia has been undertaken using different theories of phonology and probably that is the reason why a clear distinction between phonetic and phonological disturbance has not always been made. Sound disturbance in aphasia can be traced to one or more of three different disorders